2008
DOI: 10.1016/j.micres.2006.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Control of foliar diseases of mustard by Bacillus from reclaimed soil

Abstract: Bacillus subtilis strain UK-9, an isolate from reclaimed soils, was studied for its biological control activity against Alternaria leaf spot disease of mustard. In dual culture, production of antifungal metabolites by the bacteria caused morphological alterations of vegetative cells and spores, disruption and lysis of their cell wall. The antagonist reduced spore germination on leaves and disease incidence of the pathogen in plant trial as well as it also demonstrated plant-growth-promoting ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 9 publications
1
21
0
1
Order By: Relevance
“…Gnanamanickam and Mew (1992) reported high inhibition zone by Bacillus strains 4-03 and 33 against Pyricularia oryzae, a causative of blast disease of rice. Sharma and Sharma (2008) also found that B. subtilus produced antifungal compounds, which caused morphological alterations in the vegetative cells and spores, and disruption and lysis of cell walls of Alternaria species causing leaf spot of mustard. Bacillus megaterium and Pseudomonas fluorescens have been found to reduce biomass of Mycoshaerella graminicola by 43% or more in dual culture (Kildea et al, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Gnanamanickam and Mew (1992) reported high inhibition zone by Bacillus strains 4-03 and 33 against Pyricularia oryzae, a causative of blast disease of rice. Sharma and Sharma (2008) also found that B. subtilus produced antifungal compounds, which caused morphological alterations in the vegetative cells and spores, and disruption and lysis of cell walls of Alternaria species causing leaf spot of mustard. Bacillus megaterium and Pseudomonas fluorescens have been found to reduce biomass of Mycoshaerella graminicola by 43% or more in dual culture (Kildea et al, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Bacillus subtilis proved to be effective in controlling a wide range of diseases caused by fungi and bacteria, such as leaf spot caused by Alternaria brassicae (Sharma and Sharma 2006), Sclerotinia stem rot caused by Sclerotinia sclerotiorum (Zhang and Xue 2010) and crown gall caused by Agrobacterium tumefaciens (Rhouma et al 2008). Bacillus subtilis is considered to be a safe biological agent (Merriman et al 1974;Baker et al 1985;Turner and Backman 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, these cells are formed under environmental stress and improve fungus survival under adverse conditions. The formation of chlamydoconidia-shaped cells was observed after the interaction of dematiaceous fungi with B. subtilis or with bacterial metabolic products (13,14). The introduction of bacillus into 15-day cultures of F. pedrosoi caused morphological changes in the fungal hyphae, including the presence of terminal chlamydoconidiashaped cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that Bacillus spp. can induce morphological changes in dematiaceous fungi (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%